Feasibility of Pd-catalytic onto nontronite mineral and H2O2 produced from H2 and O2 to degrade organic contaminants - AlAni, Yasir (Iraqi Journal of Civil Engineering, 2017)
A novel electro-Fenton process based on Pd-catalytic production of H2O2 from H2 and O2 has been studied and examined recently for altering and degrading organic contaminants in different types of wastewaters. The study endeavors to synthesize an integrated catalyst by loading Pd onto the clay mineral,nontronite, (Pd/NTm) so that H2O2 and Fe(II)‏ can be produced simultaneously in the electrolytic system. In an undivided electrolytic cell, rhodamine B, a probe organic contaminant, is degraded by 93% within 60 min under conditions of 50 mA, 1 g/L Pd/NTm, pH 3 and 20 mg/L initial concentration. A distinct mechanism, reductive dissolution of solid Fe(III) in nontronite by atomic H chemisorbed on Pd surface, is responsible for Fe(II) ‏ production from Pd/NTm.